KODAKCoin: a blockchain revolution or exploiting a potential cryptocurrency bubble?. Issue 7 (15th April 2020) - Corbet, Shaen; Larkin, Charles; Lucey, Brian; Yarovaya, Larisa
ABSTRACT: Eastman Kodak is an American technology company that produces imaging products. In 2018, it announced its intentions to enter the crytpocurrency market, raising concerns that it could be taking advantage of a potential cryptocurrency bubble for short-term gains. We analyse the relationships between Kodak, crytocurrency and stock market index returns. We find evidence of a significant, sustained increase in both the share price and price volatility of Kodak after the KODAKCoin announcement, with an increased correlation between the price of Kodak shares and Bitcoin.